A Review Paper on Drought under Global Warming (International Journal of Innovative Research in Engineering & Management, 2023)
Dry spells ranging from years to decades  have happened many times throughout history. North  America, West Africa, and East Asia, for example, have  seen significant changes in the past century. Asia.  Droughts were most likely caused by unusual tropical sea  surface temperatures. Temperatures (SSTs), with La  Nina-like SST anomalies causing dryness in parts of the  country. Drought in East China is being caused by El  Nino-like SSTs in North America. Across  Africa, warming in the Atlantic and a southern shift of the  hottest SSTs Droughts in the Sahel have been blamed on  the Indian Ocean. Local feedbacks may be  useful. Intensify and extend the drought Since the 1970s,  global aridity has risen dramatically. Due to recent  dryness in Africa, southern Europe, and East and South  Asia in the 1970s, as well as eastern Australia. Despite  the El Nino-Southern Oscillation (ENSO), tropical  cyclones continue to exist. Atlantic SSTs and Asian  monsoons have aided the current dryness. The demand  for moisture in the atmosphere has risen because of recent  warming, and this has likely changed the landscape. Both  of these factors contribute to the drying of the  atmosphere. Models of climate change. In the twenty-first  century, much of Africa and southern Europe saw  increasing aridity and the Middle East, as well as the  majority of North and South America, Australia, and  Southeast Asia Region.
Keywords: Drought; Global Warming; ENSO; Surface; Temperature